Jesus in Asia - Sugirtharajah, R. S. (Rasiah S.) (Cambridge, Massachusetts Harvard University Press, 2018)
Reconstructions of Jesus occurred in Asia long before the Western search for the historical Jesus began in earnest. Asians remade Jesus at times appreciatively and at other times critically. R.S. Sugirtharajah situates the historical Jesus beyond the narrow confines of the West and offers an eye-opening chapter in the story of global Christianity--
Introduction: The Asian search for the historical Jesus -- Jesus in the sutras, stele, and suras -- The heavenly elder brother -- A Judean jnana guru -- The nonexistent Jesus -- A Jaffna man's Jesus -- Jesus as a Jain tirthankara -- An Upanishadic mystic -- A minjung messiah -- Jesus in a kimono -- Conclusion: Our Jesus, their Jesus
Includes bibliographical references (pages 267-303) and index
Keywords: Jesus Christ -- Oriental interpretations; Jesus Christ -- Hindu interpretations; Jesus Christ -- Humanity